Immersed tunnel technology: a brief history of its development = Tunele zatapiane: krótka historia rozwoju technologii - Łotysz, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The first tunnel made of segments, which were sunken and then merged under water, was built in 1896. It was a passage for conducting sewerage under Boston Harbor. The first tunnel for passenger traffic was constructed ten years later, also in the United States.
Keywords: tunele zatapiane; technologie tunelu zatapialnego; immersed tunnel; sunken tunnel; subaquanous tunneling